폐기물 가스화 합성가스로부터 수소 생산을 위한 고온수성가스전이 반응에서 환원 조건이 미치는 영향 - 공지현; 장원준 (환경에너지공학, 2024)
This study explores the proper reduction condition of a commercial Fe-Cr catalyst for high-temperature water-gas shift reaction from waste gasification-derived synthesis gas. We investigate CO conversion, CO2 selectivity, and stability of the HTS reaction by reducing a commercial Fe-Cr catalyst under 2% H2/N2, 5% H2/N2, and reactant gas conditions. Characteristic results of the catalysts after reduction and reaction identify the Fe species formed under different reduction conditions. Catalytic HTS reaction results after reduction under different conditions show similar CO conversion and 100% CO2 selectivity across all temperature ranges. In particular, the catalyst reduced using reactant gas also exhibited excellent CO conversion, 100% CO2 selectivity, and stability for 20 hours. This result offers that the reactant gas can be a appropriate for the reduction of catalysts without the need to proceed the pre-reduction step separately
Keywords: Reduction condition; Catalyst; High-temperature water-gas shift; Waste gasification-derived synthesis gas; Fe-Cr